Thermodynamic profile and molecular modeling of the interaction between Grb2 dimer and flavonoids Rutin and Morin - Sanches, Karoline [UNESP]; Dias, Raphael V.R. [UNESP]; da Silva, Paulo H. [UNESP]; Caruso, Icaro P. [UNESP]; Fossey, Marcelo A. [UNESP]; de Souza, Fátima P. [UNESP]; de Oliveira, Leandro C. [UNESP]; Melo, Fernando A. [UNESP] (Elsevier, 2021)
The adaptor protein growth factor-bound protein 2 (Grb2) is an important regulator of the fibroblast growth factor receptor 2 (FGFR2) before extracellular stimuli. It is known to form complexes that end up in the mitogen-activated protein kinase (MAPK) pathway activation, which is involved in proliferation and oncogenic signal transduction. Grb2 is a versatile protein performing functions other than adaptor protein, making it a relevant target to verify its interaction with flavonoids such as Rutin and Morin. These small polyphenols molecules are easy to be found in the nature and its anti-tumor properties are well-known. By using fluorescence spectroscopy, the thermodynamic profile of the interaction between those molecules and Grb2 showed entropically driven interactions, where hydrophobic effects take place as the main interaction potential. The dissociation constants found were Kd ~10−6 M for Morin and Kd ~10−5 M for Rutin. The molar ratio protein/ligand is 1:1 for both assays. Furthermore, nuclear magnetic resonance has provided important information about the protein-ligand interaction epitopes, which has been used as a guide for molecular docking and molecular dynamics simulations. The combination of the obtained results shows the SH2 domain as the most probable interaction place on Grb2 dimer for Rutin and Morin binding. Sh2 is a well-known domain responsible for pY (phosphotyrosine) recognition upon protein partners and an important protein module for testing SH2 domain inhibitors.
Keywords: Flavonoids; Grb2; Interaction; Molecular modeling; Thermodynamics